2018
DOI: 10.1101/257436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fission yeast cells overproducing HSET/KIFC1 provides a useful tool for identification and evaluation of human kinesin-14 inhibitors

Abstract: Many cancer cells contain more than two centrosomes, yet these cancer cells can form bipolar spindles and appear to proliferate normally, instead of committing lethal mitoses with multipolar spindles. It is shown that extra centrosomes are clustered into two pseudo-bipolar spindle poles, thereby escaping from multipolarity. Human kinesin-14 (HSET or KIFC1), a minus end-directed motor, plays a crucial role in centrosome clustering and as such, HSET is essential for cell viability only in cancer cells with super… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Biological inhibition or knockdown of Eg5 and overexpression of HSET are shown to alter spindle bipolarity (6,30,65,66,(81)(82)(83). We manipulate motor activity in the model by perturbing the motor-MT binding probability, which accurately captures spindle collapse with no Eg5 or HSET activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological inhibition or knockdown of Eg5 and overexpression of HSET are shown to alter spindle bipolarity (6,30,65,66,(81)(82)(83). We manipulate motor activity in the model by perturbing the motor-MT binding probability, which accurately captures spindle collapse with no Eg5 or HSET activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Biological results also show that high HSET activity increases the frequency of monopolar spindles (81)(82)(83). To test that our model accurately reflects this role of HSET activity, we mimic HSET overexpression by setting the probability of binding to MTs (P H ) equal to one.…”
Section: Motor Protein Perturbations Alter Spindle Bipolaritymentioning
confidence: 98%
“…Specifically, AZ82 decreased the viability of yeast cells despite the absence of KIFC1 in the cells. 65 However, no morphological changes were detected. Interestingly, AZ82 at 10 μM rescued cell death mediated by KIFC1 overexpression in yeast cells, further validating its binding to KIFC1 even though nonspecifically.…”
Section: Az82mentioning
confidence: 93%
“…The 1,2,4-thiadiazole derivative SR31527 (Figure 7) was identified as a KIFC1 inhibitor that targets the microtubulestimulated ATPase activity of KIFC1. 65 Among other HTS hits, SR31527 had the most potent activity (IC 50 : 6.6 μM) and favorable structural features. To assess whether SR31527 binds KIFC1 only or the complex KIFC1microtubules, Zhang et al performed a binding assay using biolayer interferometry and found that SR31527 displayed direct binding to KIFC1 with a K d of 25.4 nM.…”
Section: Sr31527mentioning
confidence: 98%
See 1 more Smart Citation